Duality in the Aljama. Muslim Landowners and Businessmen. The Case of Valencian Region «El Comtat» (Second Half of 15th Century) - Llibrer Escrig, José Antonio (Anaquel de Estudios Árabes, 2014)
This article studies the socioeconomic differences inside muslim aljamas in the Kingdom of Valencia during the second half of the fifteenth century. Islamic communities were not homogeneous like historiography has shown. In these rural communities there were not only one group of landless farmers, there were also others social differences inside. With the example of «El Comtat», southern interior region of Valencia, we explain how the social and economic duality was born in the muslim aljamas through the study of land market and agricultural products sales. So we can research directly the process of consolidation of the muslim rural elites with peasant landowners and Businessmen.